Negative active material and preparation method thereof, negative pole piece, battery and power utilization device
By introducing porous structures, sulfur-doped hard carbon-metal oxide materials and polyaniline shell layers into the graphite-based anode material to form a composite core-shell structure, the problem of insufficient performance of graphite-based anode material in lithium-ion batteries is solved, and a comprehensive improvement in battery capacity, magnification and cycling performance is achieved.
Patent Information
- Application Number
- CN202411815358.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
Graphite-based negative electrode materials have problems in lithium-ion batteries with low capacity, large expansion of lithium embedded, unstable structure and easy lithium removal under fast charging conditions, which affect the battery's capacity performance, rate performance and cycle performance.
Porous graphite is used as the core, and sulfur-doped hard carbon-metal oxide material is embedded in its pores, and a polyaniline material shell is added to form a composite core-shell structural material. This material improves the overall performance of the battery by increasing the specific surface area, forming a conductive network with high ionic conductivity, alleviating the expansion of embedded lithium and enhancing structural stability.
At the same time, the capacity, rate and cycle performance of the battery are improved, and the comprehensive improvement of material performance is achieved, and the defect that traditional modification methods cannot improve multiple performances at the same time.
Smart Images

Figure CN119650641A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode active material and a preparation method thereof, a negative electrode sheet, a battery, and an electrical device. Background Art
[0002] Lithium-ion batteries are widely used in consumer electronics, energy storage devices, electric vehicles and other fields due to their high energy density, long cycle life and low self-discharge rate. Among them, the negative electrode material is responsible for storing and releasing electrical energy during the charging and discharging process, and its performance directly affects the battery's energy density, operating voltage and overall efficiency.
[0003] As the mainstream negative electrode material in the lithium battery industry, graphite has the advantages of strong lithium insertion ability, good conductivity, good safety performance, and low price. However, graphite materials have problems such as low actual gram capacity (300mAh / g~360mAh / g), large lithium insertion expansion, unstable brittle structure, and easy lithium precipitation under fast charging conditions, which affect the battery's capacity performance, rate performance, and cycle performance.
[0004] In traditional technology, graphite is modified by surface coating or metal doping, but these modification methods can only improve the performance of one aspect of the material, and cannot achieve simultaneous improvement in capacity performance, rate performance and cycle performance. Summary of the invention
[0005] Based on this, it is necessary to provide a negative electrode active material and its preparation method, a negative electrode plate, a battery, and an electrical device to improve the structural stability of graphite-based negative electrode active materials, increase lithium insertion active sites, and improve the ion conductivity of the material, thereby simultaneously improving the capacity performance, rate performance, and cycle performance of the battery.
[0006] The first aspect of the present application provides a negative electrode active material, which includes: an inner core, including porous graphite and sulfur-doped hard carbon-metal oxide material, the sulfur-doped hard carbon-metal oxide material is arranged in the pores of the porous graphite; and a shell layer, coating at least a portion of the surface of the inner core, the shell layer including a polyaniline material.
[0007] In some embodiments, the shell layer has a thickness of 5 nm to 20 nm.
[0008] In some embodiments, the negative electrode active material has an electrical conductivity of 6.50 S / cm to 8.55 S / cm.
[0009] In some embodiments, the tap density of the negative electrode active material is 1.12 g / cm 3 ~1.22g / cm 3 .
[0010] In some embodiments, the specific surface area of the negative electrode active material is 1.65 m 2 / g~1.95m 2 / g.
[0011] The second aspect of the present application provides a method for preparing a negative electrode active material, which comprises the following steps: dispersing porous graphite in a lignin sulfonate solution, adding a metal salt solution, drying and heat treating the solution to obtain an inner core; coating the inner core with a shell containing a polyaniline material to obtain an negative electrode active material; wherein the inner core comprises porous graphite and a sulfur-doped hard carbon-metal oxide material, and the sulfur-doped hard carbon-metal oxide material is disposed in the pores of the porous graphite.
[0012] In some embodiments, porous graphite is prepared by the following steps: mixing graphite, a pore former and a template molecule, calcining the mixture, and then removing the template molecule to obtain porous graphite; wherein the template molecule is selected from at least one of lignin and a lignin derivative.
[0013] In some embodiments, the mass ratio of graphite, pore former and template molecule is 100:(1-5):(1-5).
[0014] In some embodiments, the concentration of the lignin sulfonate solution is 1 wt % to 5 wt %.
[0015] In some embodiments, the mass ratio of porous graphite to metal salt in the metal salt solution is 100:(0.1-1.0).
[0016] In some embodiments, the metal salt in the metal salt solution is selected from at least one of chlorides or sulfates of Cu, Ti, Ni, Co, Fe or Mn.
[0017] In some embodiments, the maximum value of the temperature of the heat treatment is 500°C to 1000°C.
[0018] The third aspect of the present application provides a negative electrode plate, which includes the negative electrode active material provided by the first aspect above, or the negative electrode active material prepared by the preparation method provided by the second aspect above.
[0019] A fourth aspect of the present application provides a battery, which includes the negative electrode plate provided by the third aspect.
[0020] A fifth aspect of the present application provides an electrical device, which includes the battery provided by the fourth aspect.
[0021] Compared with the traditional technology, this application has at least the following beneficial effects:
[0022] The negative electrode active material provided by the present application has a synergistic effect among the porous structure of graphite, the sulfur-doped hard carbon-metal oxide material and the shell containing polyaniline material. On the one hand, the porous structure of graphite can increase the specific surface area and provide more lithium insertion active sites. At the same time, the sulfur-doped hard carbon-metal oxide material forms a high ionic conductivity and ion conductive network. The combined metal oxide capacity is higher than that of graphite, which can provide more energy for the insertion and release of lithium ions, improve the capacity performance and rate performance of the battery, and overcome the problem of the first coulomb efficiency decrease when the specific surface increases. The shell containing polyaniline material coated on the surface of the inner core can give play to the advantages of the conductivity of conductive polyaniline and further improve the lithium storage characteristics of the material. On the other hand, the porous structure and the shell containing polyaniline material can alleviate the expansion of lithium insertion, and the sulfur-doped hard carbon-metal oxide material is embedded in the porous structure, which improves the structural stability and tap density of the material. The composite core-shell structure material also enhances the ability to absorb and retain liquid, which is very beneficial to the maintenance and recovery of the battery capacity in the later stage of the cycle, thereby improving the cycle performance of the battery.
[0023] Therefore, compared with traditional graphite-based negative electrode materials, the negative electrode active material provided in the present application improves the capacity performance, rate performance and cycle performance of the battery at the same time, achieving a comprehensive improvement in material performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the structure of the negative electrode active material in one embodiment of the present application.
[0025] Figure 2 Schematic diagram of a process for preparing a negative electrode active material in one embodiment of the present application.
[0026] 1. Negative electrode active material; 10. Core; 11. Porous graphite; 12. Sulfur-doped hard carbon-metal oxide material; 20. Shell. DETAILED DESCRIPTION
[0027] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0028] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features, and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.
[0029] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0030] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0033] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0034] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0035] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0036] See also Figure 1 As shown, the first aspect of the present application provides a negative electrode active material 1, which includes a core 10 and a shell 20. The core 10 includes a porous graphite 11 and a sulfur-doped hard carbon-metal oxide material 12, and the sulfur-doped hard carbon-metal oxide material 12 is arranged in the pores of the porous graphite 11. The shell 20 is coated on at least part of the surface of the core 10, and the shell 20 includes a polyaniline material.
[0037] The negative electrode active material 1 provided in the present application has a synergistic effect among the porous structure of graphite, the sulfur-doped hard carbon-metal oxide material 12, and the shell layer 20 containing the polyaniline material. On the one hand, the porous structure of graphite can increase the specific surface area and provide more active sites for lithium insertion. At the same time, the sulfur-doped hard carbon-metal oxide material 12 forms a high ionic conductivity and ionic conductive network. The capacity of the metal oxide is higher than that of graphite, which can provide more energy for the insertion and release of lithium ions, improve the capacity performance and rate performance of the battery, and overcome the problem of the first coulomb efficiency decrease when the specific surface increases. The shell layer 20 containing the polyaniline material is coated on the surface of the inner core 10, which can give play to the advantages of the conductivity of the conductive polyaniline and further improve the lithium storage characteristics of the material. On the other hand, the porous structure and the shell layer 20 containing the polyaniline material can alleviate the expansion of lithium insertion. The sulfur-doped hard carbon-metal oxide material 12 is embedded in the porous structure, which improves the structural stability and tap density of the material. The composite core-shell structure material also enhances the ability to absorb and retain liquid, which is very beneficial to the maintenance and recovery of the battery capacity in the later stage of the cycle, thereby improving the cycle performance of the battery.
[0038] Therefore, compared with traditional graphite-based negative electrode materials, the negative electrode active material 1 provided in the present application improves the capacity performance, rate performance and cycle performance of the battery at the same time, achieving a comprehensive improvement in material performance.
[0039] Herein, the “porous graphite 11 ” refers to a graphite material having a plurality of pore structures on the surface thereof that are connected to the inside thereof.
[0040] Herein, the "sulfur-doped hard carbon-metal oxide material 12" refers to a composite material of sulfur-doped hard carbon and metal oxide.
[0041] In some embodiments, the thickness of the shell 20 is 5 nm to 20 nm. For example, the thickness of the shell 20 can be, but is not limited to, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, and 20 nm. Within the above thickness range, the shell 20 can inhibit the expansion of the core 10, improve the structural stability, and maintain good conductivity.
[0042] In some embodiments, the conductivity of the negative electrode active material 1 is 6.50S / cm to 8.55S / cm. For example, the conductivity of the negative electrode active material 1 may be, but is not limited to, 6.50S / cm, 6.85S / cm, 7.00S / cm, 7.10S / cm, 7.20S / cm, 7.30S / cm, 7.40S / cm, 7.50S / cm, 7.55S / cm, 7.60S / cm, 7.70S / cm, 7.80S / cm, 7.90S / cm, 8.00S / cm, 8.50S / cm, 8.55S / cm. The conductivity within the above range can ensure high rate performance without affecting the structural stability and cycle performance of the material.
[0043] In some embodiments, the tap density of the negative electrode active material 1 is 1.12 g / cm 3 ~1.22g / cm 3 For example, the tap density of the negative electrode active material 1 may be, but is not limited to, 1.12 g / cm 3 , 1.14g / cm 3 , 1.16g / cm 3 , 1.18g / cm 3 , 1.20g / cm 3 , 1.22g / cm 3 When the tap density is within the above range, the negative electrode active material 1 can have a higher ion transport capacity, a higher gram capacity and a lower side reaction. Therefore, an appropriate tap density can improve the rate performance and cycle performance of the battery.
[0044] In some embodiments, the specific surface area of the negative electrode active material 1 is 1.65 m 2 / g~1.95m 2 / g. For example, the specific surface area of the negative electrode active material 1 may be, but is not limited to, 1.65 m 2 / g, 1.70m 2 / g, 1.75m 2 / g, 1.80m 2 / g, 1.85m 2 / g, 1.90m2 / g, 1.95m 2 When the specific surface area is within the above range, the negative electrode active material 1 can provide sufficient reaction sites, increase the active sites for lithium ion embedding and de-embedding, and avoid the loss of the first coulombic efficiency caused by an excessively large specific surface area.
[0045] The second aspect of the present application provides a method for preparing a negative electrode active material, such as Figure 2 As shown, the preparation method comprises the following steps:
[0046] S1. The porous graphite is dispersed in a lignin sulfonate solution, and then a metal salt solution is added, and the mixture is dried and heat treated to obtain a core.
[0047] S2. The inner core is coated with a shell layer containing polyaniline material to obtain a negative electrode active material.
[0048] The inner core includes porous graphite and sulfur-doped hard carbon-metal oxide material, and the sulfur-doped hard carbon-metal oxide material is arranged in the pores of the porous graphite.
[0049] The preparation method of the negative electrode active material provided in the present application, on the one hand, lignin sulfonate acts as a surface modifier and dispersant to evenly disperse the porous graphite, avoid the agglomeration of graphite particles, and coordinates with metal ions to control and modify the growth of nanoparticles, and on the other hand, after heat treatment, it coordinates with metal ions to form sulfur-doped hard carbon-metal oxide materials, and evenly embeds them into the pores of porous graphite. Then, by coating the shell layer containing polyaniline material, additional protection is provided for the inner core, and the conductive performance of the negative electrode material is improved. In addition, the preparation method is relatively simple in process, easy to control in operation, and the raw material source is abundant and low in price, which is suitable for industrial application.
[0050] In some embodiments, in step S1, the concentration of the lignin sulfonate solution is 1wt% to 5wt%, including but not limited to 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, and 5wt%.
[0051] In some embodiments, in step S1, the mass ratio of porous graphite to metal salt in the metal salt solution is 100:(0.1-1.0).
[0052] In some embodiments, in step S1, the metal salt in the metal salt solution is selected from at least one of chlorides or sulfates of Cu, Ti, Ni, Co, Fe or Mn.
[0053] In some embodiments, in step S1, the maximum value of the heat treatment temperature is 500° C. to 1000° C. For example, the maximum value of the heat treatment temperature may be, but is not limited to, 500° C., 600° C., 700° C., 800° C., 900° C., and 1000° C. The maximum value of the heat treatment temperature within the above range is conducive to forming the sulfur-doped hard carbon-metal oxide material and uniformly embedding it into the pores of the porous graphite.
[0054] Furthermore, the heat treatment is a step-by-step heat treatment. The step-by-step heat treatment includes a first stage, a second stage and a third stage, the temperature of the first stage is 200°C to 300°C, the temperature of the second stage is 300°C to 500°C, and the temperature of the third stage is 500°C to 1000°C. The treatment time of the first stage, the second stage and the third stage is 2h to 4h. The step-by-step heat treatment method helps to control the thermal decomposition process of the material and avoid the destruction of the material structure due to too fast temperature changes.
[0055] In some embodiments, in step S1, the heat treatment is performed under an inert atmosphere; the inert atmosphere is selected from nitrogen, argon or helium.
[0056] In some embodiments, the porous graphite is prepared by the following steps: mixing graphite, a pore-forming agent and a template molecule, calcining the mixture, and then removing the template molecule to obtain the porous graphite, wherein the template molecule is selected from at least one of lignin and a lignin derivative.
[0057] In this embodiment, adding lignin or a lignin derivative as a template can control the pore size and pore size distribution of the porous graphite during the calcination process. On the one hand, it makes the pore size distribution of the porous graphite more uniform; on the other hand, based on the structural similarity between lignin or a lignin derivative and lignin sulfonate, the pore size formed by using lignin or a lignin derivative as a template molecule also matches the sulfur-doped hard carbon material synthesized using lignin sulfonate.
[0058] Herein, the "lignin derivative" refers to a compound having a unit structure constituting lignin or having a structure similar to a unit structure constituting lignin.
[0059] In some embodiments, the pore-forming agent is selected from at least one of potassium hydroxide, ammonium carbonate, potassium gluconate, and sodium dihydrogen citrate.
[0060] In some embodiments, the mass ratio of graphite, pore former and template molecule is 100:(1-5):(1-5).
[0061] In some embodiments, the graphite is natural graphite or artificial graphite.
[0062] In some embodiments, calcination is performed under an inert atmosphere; the inert atmosphere is selected from nitrogen, argon or helium.
[0063] In some embodiments, the calcined product is acid-washed and water-washed to neutrality.
[0064] In some embodiments, step S2 specifically includes the following steps: mixing the core, aniline, initiator and protonic acid in a solvent, and then reacting them in an ice bath to in-situ coat the surface of the core with a shell layer containing polyaniline material to obtain a negative electrode active material.
[0065] In some embodiments, the initiator includes at least one of ammonium persulfate, benzoyl peroxide, ferric chloride and hydrogen peroxide.
[0066] In some embodiments, the protonic acid includes at least one of p-toluenesulfonic acid, hydrochloric acid, and camphorsulfonic acid.
[0067] The third aspect of the present application provides a negative electrode plate, which includes the negative electrode active material provided by the first aspect above, or the negative electrode active material prepared by the preparation method provided by the second aspect above.
[0068] Generally speaking, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer is arranged on at least one side of the negative electrode current collector. The negative electrode active material layer includes the negative electrode active material provided by the first aspect above, or the negative electrode active material prepared by the preparation method provided by the second aspect above.
[0069] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0070] In some embodiments, the negative electrode active material layer may further include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), or carboxymethyl chitosan (CMCS).
[0071] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.
[0072] In some of the embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0073] A fourth aspect of the present application provides a battery, which includes the negative electrode plate provided by the third aspect.
[0074] In some embodiments, the battery comprises a lithium ion battery or a sodium ion battery. The battery of the present application comprises a battery cell form, a battery module form and a battery pack form.
[0075] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0076] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, the positive electrode active material layer is disposed on at least one side of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.
[0077] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.
[0078] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0079] In some embodiments, the positive electrode active material layer may further include a positive electrode active material. The positive electrode active material may be a positive electrode active material for a battery known in the art.
[0080] As an example, when the positive electrode plate is used in a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries known in the art. Further, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) or at least one of its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0081] In some embodiments, the positive electrode active material layer may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0082] In some embodiments, based on the total mass of the positive electrode active material layer, the mass proportion of the binder is 0.5% to 3%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc.
[0083] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0084] In some embodiments, based on the total mass of the positive electrode active material layer, the mass proportion of the conductive agent is 0.8% to 4%, for example, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, etc.
[0085] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0086] The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0087] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0088] In some of the embodiments, when the battery is a lithium ion battery, the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0089] In some embodiments, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone and diethyl sulfone.
[0090] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0091] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0092] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0093] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.
[0094] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0095] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and the plastic may be polypropylene, polybutylene terephthalate, polybutylene succinate, etc.
[0096] A fifth aspect of the present application provides an electrical device, which includes the battery provided by the fourth aspect.
[0097] Batteries can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Among them, mobile devices may be, for example, mobile phones, laptops, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.
[0098] The present application will be further described below with reference to specific embodiments and comparative examples.
[0099] Example 1
[0100] Negative electrode active material:
[0101] 1) 10 g of graphite, 0.25 g of pore-forming agent potassium hydroxide and 0.25 g of template molecule lignin were mixed and calcined in an argon atmosphere for 5 h. The obtained product was alternately washed with 0.05 mol / L hydrochloric acid solution and deionized water until neutral, thereby removing the template molecule lignin, and then vacuum dried at 80° C. for 8 h to obtain porous graphite.
[0102] 2) 8 g of the porous graphite prepared above was added to 80 mL of a 2 wt% sodium lignin sulfonate solution, and a CuCl2 aqueous solution (prepared by dissolving 0.04 g of CuCl2 solid in 20 mL of deionized water) was slowly added in a nitrogen atmosphere. After being fully stirred, the mixture was dried at 110° C. and then heat-treated step by step: the first stage was heat-treated at 250° C. for 5 h, the second stage was heat-treated at 400° C. for 4 h, and the third stage was heat-treated at 800° C. for 4 h to obtain a core.
[0103] The mass ratio of porous graphite to metal salt in the metal salt solution is 100:0.5; the inner core includes porous graphite and sulfur-doped hard carbon-metal oxide material, and the sulfur-doped hard carbon-metal oxide material is arranged in the pores of the porous graphite.
[0104] 3) 5 g of the prepared core and 0.57 g of p-toluenesulfonic acid were uniformly dispersed in deionized water, 0.40 g of aniline was added and placed in an ice bath environment, and ammonium persulfate solution (prepared by dissolving 0.52 g of ammonium persulfate in 30 mL of deionized water) was slowly added dropwise. After stirring for 8 hours, the mixture was centrifuged and washed with anhydrous ethanol and deionized water in turn. After vacuum drying, a shell layer containing polyaniline material was coated on the surface of the core to obtain a negative electrode active material.
[0105] The thickness of the shell layer is 10 nm.
[0106] Negative electrode:
[0107] The negative electrode sheet includes a negative electrode current collector copper foil and a negative electrode active material layer. The negative electrode active material layer (the mass ratio of negative electrode active material, conductive carbon black, CMC and SBR is 96.0:1.0:1.2:1.8) is arranged on one side of the negative electrode current collector. The negative electrode active material layer includes the above-mentioned negative electrode active material.
[0108] Battery:
[0109] The battery includes a positive electrode plate made of lithium iron phosphate (the mass ratio of lithium iron phosphate, PVDF, conductive carbon black and carbon nanotubes is 97.2:1.8:0.5:0.5), the above-mentioned negative electrode plate, LiPF6 (the solvent is EC+EMC, the volume ratio is 1:1, the concentration is 1.2 mol / L) electrolyte and a PE separator.
[0110] Example 2
[0111] The preparation method of the negative electrode active material, the negative electrode plate and the battery in this embodiment is basically the same as that in embodiment 1, except that:
[0112] In step 2), the temperature of the third stage of heat treatment is 500°C.
[0113] Example 3
[0114] The preparation method of the negative electrode active material, the negative electrode plate and the battery in this embodiment is basically the same as that in embodiment 1, except that:
[0115] In step 2), the temperature of the third stage of heat treatment is 1000°C.
[0116] Example 4
[0117] The preparation method of the negative electrode active material, the negative electrode plate and the battery in this embodiment is basically the same as that in embodiment 1, except that:
[0118] In step 2), the concentration of the lignin sulfonate solution is 1 wt%.
[0119] Example 5
[0120] The preparation method of the negative electrode active material, the negative electrode plate and the battery in this embodiment is basically the same as that in embodiment 1, except that:
[0121] In step 2), the concentration of the lignin sulfonate solution is 5 wt%.
[0122] Example 6
[0123] The preparation method of the negative electrode active material, the negative electrode plate and the battery in this embodiment is basically the same as that in embodiment 1, except that:
[0124] In step 2), the mass of the metal salt in the metal salt solution is 0.008 g, the mass ratio of the porous graphite to the metal salt in the metal salt solution is 100:0.1, and the metal salt is replaced by FeCl3.
[0125] Example 7
[0126] The preparation method of the negative electrode active material, the negative electrode plate and the battery in this embodiment is basically the same as that in embodiment 1, except that:
[0127] In step 2), the mass of the metal salt in the metal salt solution is 0.008 g, the mass ratio of the porous graphite to the metal salt in the metal salt solution is 100:0.1, and the metal salt is replaced by NiSO4.
[0128] Example 8
[0129] The preparation method of the negative electrode active material, the negative electrode plate and the battery in this embodiment is basically the same as that in embodiment 1, except that:
[0130] In step 3), the mass of aniline is 0.10 g and the thickness of the shell is 5 nm.
[0131] Example 9
[0132] The preparation method of the negative electrode active material, the negative electrode plate and the battery in this embodiment is basically the same as that in embodiment 1, except that:
[0133] In step 3), the mass of aniline is 0.60 g and the thickness of the shell is 20 nm.
[0134] Example 10
[0135] The preparation method of the negative electrode active material, the negative electrode plate and the battery in this embodiment is basically the same as that in embodiment 1, except that:
[0136] In step 2), the temperature of the third stage of heat treatment is 450°C.
[0137] Embodiment 11
[0138] The preparation method of the negative electrode active material, the negative electrode plate and the battery in this embodiment is basically the same as that in embodiment 1, except that:
[0139] In step 2), the temperature of the third stage of heat treatment is 1100°C.
[0140] Example 12
[0141] The preparation method of the negative electrode active material, the negative electrode plate and the battery in this embodiment is basically the same as that in embodiment 1, except that:
[0142] In step 1), no template molecule lignin is added.
[0143] Comparative Example 1
[0144] Negative electrode active material:
[0145] Commercially available graphite material (manufacturer: Shijiazhuang Shangtai Technology Co., Ltd., brand: ST-72EK).
[0146] Negative electrode:
[0147] The negative electrode sheet comprises a negative electrode current collector copper foil and a negative electrode active material layer. The negative electrode active material layer is arranged on one side of the negative electrode current collector. The negative electrode active material layer comprises the above-mentioned negative electrode active material.
[0148] Battery:
[0149] The battery includes a positive electrode plate made of lithium iron phosphate, the above-mentioned negative electrode plate, a LiPF6 (solvent is EC+EMC, volume ratio 1:1, concentration 1.2 mol / L) electrolyte and a PE diaphragm.
[0150] Comparative Example 2
[0151] Negative electrode active material:
[0152] 1) Add 8 g of graphite to 80 mL of a 2 wt% sodium lignin sulfonate solution, slowly add a CuCl2 aqueous solution (prepared by dissolving 0.04 g of CuCl2 solid in 20 mL of deionized water) in a nitrogen atmosphere, stir thoroughly, dry at 110°C, and then heat treat step by step: the first stage is heat treated at 250°C for 5 h, the second stage is heat treated at 400°C for 4 h, and the third stage is heat treated at 800°C for 4 h to obtain a sulfur-doped hard carbon-metal oxide material-coated graphite material.
[0153] Wherein, the mass ratio of graphite to metal salt in the metal salt solution is 100:0.5.
[0154] 2) 5 g of the sulfur-doped hard carbon-metal oxide material coated graphite material prepared above and 0.57 g of p-toluenesulfonic acid were uniformly dispersed in deionized water, 0.40 g of aniline was added and placed in an ice bath environment, and ammonium persulfate solution (prepared by dissolving 0.52 g of ammonium persulfate in 30 mL of deionized water) was slowly added dropwise. After stirring for 8 hours, the mixture was centrifuged and washed with anhydrous ethanol and deionized water in turn. After vacuum drying, the surface of the graphite material coated with the sulfur-doped hard carbon-metal oxide material was coated with a polyaniline shell layer to obtain a negative electrode active material.
[0155] The thickness of the shell layer is 10 nm.
[0156] Negative electrode:
[0157] The negative electrode sheet includes a negative electrode current collector copper foil and a negative electrode active material layer. The negative electrode active material layer (the mass ratio of negative electrode active material, conductive carbon black, CMC and SBR is 96.0:1.0:1.2:1.8) is arranged on one side of the negative electrode current collector. The negative electrode active material layer includes the above-mentioned negative electrode active material.
[0158] Battery:
[0159] The battery includes a positive electrode plate made of lithium iron phosphate, the above-mentioned negative electrode plate (lithium iron phosphate, PVDF, conductive carbon black and carbon nanotubes have a mass ratio of 97.2:1.8:0.5:0.5), LiPF6 (the solvent is EC+EMC, the volume ratio is 1:1, the concentration is 1.2 mol / L) electrolyte and a PE separator.
[0160] Comparative Example 3
[0161] Negative electrode active material:
[0162] 1) 10 g of graphite, 0.25 g of pore-forming agent potassium hydroxide and 0.25 g of template molecule lignin were mixed and calcined in an argon atmosphere for 5 h. The obtained product was alternately washed with 0.05 mol / L hydrochloric acid solution and deionized water until neutral, thereby removing the template molecule lignin, and then vacuum dried at 80° C. for 8 h to obtain porous graphite.
[0163] 2) 8 g of the porous graphite prepared above was added to 80 mL of a 2 wt% sodium lignin sulfonate solution, and a CuCl2 aqueous solution (prepared by dissolving 0.04 g of CuCl2 solid in 20 mL of deionized water) was slowly added in a nitrogen atmosphere. After being fully stirred, it was dried at 110°C, and then heat-treated step by step: the first stage was heat-treated at 250°C for 5 h, the second stage was heat-treated at 400°C for 4 h, and the third stage was heat-treated at 800°C for 4 h to obtain a negative electrode active material.
[0164] The mass ratio of porous graphite to metal salt in the metal salt solution is 100:0.5; the negative electrode active material includes porous graphite and sulfur-doped hard carbon-metal oxide material, and the sulfur-doped hard carbon-metal oxide material is arranged in the pores of the porous graphite.
[0165] Negative electrode:
[0166] The negative electrode sheet includes a negative electrode current collector copper foil and a negative electrode active material layer. The negative electrode active material layer (the mass ratio of negative electrode active material, conductive carbon black, CMC and SBR is 96.0:1.0:1.2:1.8) is arranged on one side of the negative electrode current collector. The negative electrode active material layer includes the above-mentioned negative electrode active material.
[0167] Battery:
[0168] The battery includes a positive electrode plate made of lithium iron phosphate (the mass ratio of lithium iron phosphate, PVDF, conductive carbon black and carbon nanotubes is 97.2:1.8:0.5:0.5), the above-mentioned negative electrode plate, LiPF6 (the solvent is EC+EMC, the volume ratio is 1:1, the concentration is 1.2 mol / L) electrolyte and a PE separator.
[0169] Comparative Example 4
[0170] Negative electrode active material:
[0171] 1) 10 g of graphite, 0.25 g of pore-forming agent potassium hydroxide and 0.25 g of template molecule lignin were mixed and calcined in an argon atmosphere for 5 h. The obtained product was alternately washed with 0.05 mol / L hydrochloric acid solution and deionized water until neutral, thereby removing the template molecule lignin, and then vacuum dried at 80° C. for 8 h to obtain porous graphite.
[0172] 2) 8 g of the porous graphite prepared above was added to 80 mL of a 2 wt% sodium lignin sulfonate solution, dried at 110° C., and then heat treated step by step: the first stage was heat treated at 250° C. for 5 h, the second stage was heat treated at 400° C. for 4 h, and the third stage was heat treated at 800° C. for 4 h to obtain the inner core.
[0173] The inner core includes porous graphite and sulfur-doped hard carbon, and the sulfur-doped hard carbon is arranged in the pores of the porous graphite.
[0174] 3) 5 g of the prepared core and 0.57 g of p-toluenesulfonic acid were uniformly dispersed in deionized water, 0.40 g of aniline was added and placed in an ice bath environment, and ammonium persulfate solution (prepared by dissolving 0.52 g of ammonium persulfate in 30 mL of deionized water) was slowly added dropwise. After stirring for 8 hours, the mixture was centrifuged and washed with anhydrous ethanol and deionized water in turn. After vacuum drying, a shell layer containing polyaniline material was coated on the surface of the core to obtain a negative electrode active material.
[0175] The thickness of the shell layer is 10 nm.
[0176] Negative electrode:
[0177] The negative electrode sheet includes a negative electrode current collector copper foil and a negative electrode active material layer. The negative electrode active material layer (the mass ratio of negative electrode active material, conductive carbon black, CMC and SBR is 96.0:1.0:1.2:1.8) is arranged on one side of the negative electrode current collector. The negative electrode active material layer includes the above-mentioned negative electrode active material.
[0178] Battery:
[0179] The battery includes a positive electrode plate made of lithium iron phosphate (the mass ratio of lithium iron phosphate, PVDF, conductive carbon black and carbon nanotubes is 97.2:1.8:0.5:0.5), the above-mentioned negative electrode plate, LiPF6 (the solvent is EC+EMC, the volume ratio is 1:1, the concentration is 1.2 mol / L) electrolyte and a PE separator.
[0180] Performance Testing
[0181] (1) Conductivity, tap density and specific surface area tests
[0182] The negative electrode active materials of the above embodiments and comparative examples were measured according to the method of GB / T 24533-2019 "Graphite-based negative electrode materials for lithium-ion batteries". The test results are shown in Table 1.
[0183] Table 1
[0184]
[0185]
[0186] (2) Electrochemical performance test
[0187] a) Cycle performance: The battery prepared in the above embodiment and comparative example was charged to 3.65V at 1C constant current, constant voltage to 0.05C, and discharged to 2.5V at 1C, and the number of cycles was 1000. The DCR, capacity retention rate and full charge rebound rate at 50% SOC were measured respectively. Among them, the full charge rebound rate (%) = (thickness of the negative electrode sheet at 100% SOC after 1000 cycles - thickness of the negative electrode sheet after rolling) / thickness of the electrode sheet after rolling * 100%.
[0188] b) Rate performance: The batteries prepared in the above embodiments and comparative examples were first charged at a constant current of 2C to 3.65V, then charged at a constant voltage to a current less than 0.05C, and then discharged at 0.33C to 2.5V to obtain the discharge capacity. The ratio of the capacity charged in the constant current section to the total charge capacity was calculated to obtain the constant current charge ratio at the 2C charge rate.
[0189] The test results are shown in Table 2.
[0190] Table 2
[0191]
[0192]
[0193] As shown in Table 1 and Table 2, by comparing Examples 1 to 12 and Comparative Examples 1 to 4, it can be seen that the negative electrode active material provided in the present application improves the conductivity, tap density and specific surface area of the material, thereby improving the cycle performance and rate performance of the battery.
[0194] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0195] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the technical concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A negative electrode active material, characterized in that: include: The inner core includes porous graphite and sulfur-doped hard carbon-metal oxide material, wherein the sulfur-doped hard carbon-metal oxide material is disposed in the pores of the porous graphite; as well as The shell layer is coated on at least a portion of the surface of the core, and the shell layer comprises a polyaniline material.
2. The negative electrode active material according to claim 1, characterized in that The thickness of the shell layer is 5nm to 20nm.
3. The negative electrode active material according to claim 1 or 2, characterized in that: The negative electrode active material satisfies at least one of the following conditions: (1) The conductivity of the negative electrode active material is 6.50 S / cm to 8.55 S / cm; (2) The tap density of the negative electrode active material is 1.12 g / cm 3 ~1.22g / cm 3 ; (3) The specific surface area of the negative electrode active material is 1.65 m 2 / g~1.95m 2 / g.
4. A method for preparing a negative electrode active material, characterized in that: The following steps are involved: The porous graphite is dispersed in a lignin sulfonate solution, a metal salt solution is added, and the mixture is dried and heat treated to obtain a core; Coating a shell layer containing polyaniline material on the surface of the core to obtain a negative electrode active material; Wherein, the inner core comprises the porous graphite and the sulfur-doped hard carbon-metal oxide material, and the sulfur-doped hard carbon-metal oxide material is arranged in the pores of the porous graphite.
5. The method for preparing the negative electrode active material according to claim 4, characterized in that: The porous graphite is prepared by the following steps: Calcining the mixture of graphite, a pore former and a template molecule, and then removing the template molecule to obtain the porous graphite; Wherein, the template molecule is selected from at least one of lignin and lignin derivatives.
6. The method for preparing the negative electrode active material according to claim 5, characterized in that: The mass ratio of the graphite, the pore former and the template molecule is 100:(1-5):(1-5).
7. The method for preparing the negative electrode active material according to claim 4, characterized in that: The step of dispersing porous graphite into a lignin sulfonate solution, adding a metal salt solution, drying and heat treating the resultant core satisfies at least one of the following conditions: (1) The concentration of the lignin sulfonate solution is 1wt% to 5wt%; (2) The mass ratio of the porous graphite to the metal salt in the metal salt solution is 100:(0.1-1.0); (3) The metal salt in the metal salt solution is selected from at least one of chlorides or sulfates of Cu, Ti, Ni, Co, Fe or Mn; (4) The maximum value of the temperature of the heat treatment is 500°C to 1000°C.
8. A negative electrode plate, characterized in that: The invention comprises the negative electrode active material according to any one of claims 1 to 3, or the negative electrode active material prepared by the preparation method according to any one of claims 4 to 7.
9. A battery, characterized in that: Comprising the negative electrode sheet as described in claim 8.
10. An electrical device, characterized in that: Comprising the battery as claimed in claim 9.
Citation Information
Cited By
Graphite negative electrode material and preparation method and application thereof
CN120453322A
Composite current collector and preparation method and application thereof
CN120657138A